RELATIONSHIP WITH MOTHER WORKING WITH EARLY REMAINING INDOROWATI VILLAGE DISTRICT EAST DISTRICT NORTH LAMPUNG DISTRICT IN 2017 - Santi Mutiara; Yona Desni Sagita (Jurnal Gizi Aisyah, 2018)
WHO recorded the world's IMR rate of 35 per 1000 live births. This figure is still far below the target of the fifth Millennium Development Goal (MDGs), which is 23 per 1000 live births in 2015. "That is, every one hour 10 Indonesian babies die and every 6 minutes 1 Indonesian baby dies from not getting milk from his mother at one The first hour of birth (WHO 2015).Based on prasurvey conducted from 10 mothers who have babies aged 6-2 years there are 7 (70%) babies who experience early weaning and 3 (30%) babies not weaning early. And prasurvey results from 10 mothers were 6 (60%) working mothers and 4 (4%) did not work. From the above data the authors are interested to examine the relationship of working mothers with early weaning of infants in the village dorowati abung district east of northern Lampung district in 2017. This study used a kind of correlation analytical research with cross sectional approach. The population in this study were all mothers who had infants numbered 118 who were aged 6-2 years in dorowati village, east abung district, northern lampung district in 2017.Known frequency distribution of early weaning occurrences in infants in dorowati village, east abung district, northern lampung district in 2017.Known the distribution of working mothers in the village dorowati sub-district abung east district of northern Lampung 2017. Known maternal relations work with early weaning of infants in the village dorowati abung subdistrict east of northern Lampung district in 2017. In the statistical calculation results show the relationship between working mother with weaning early. Where X2 count 23,87 ≥ ​​from X2 table 2,706 with error rate 0,01 and with df = (b-1) (k-1) = (2-1) (2-1) = 1. Suggestions expected by researcher To health workers to provide counseling to mothers about appropriate weanings to babies.